Predictability of Burnout in perceived self-competence among Mothers of Students with Disabilities at Sultanate of Oman (Journal Of Educational and Psychological Researches, 2023)
AbstractThe current study aims to identify the predictability of burnout in perceived self-competence among mothers of students with disabilities in the Sultanate of Oman. The study sample consists of (484) respondents who were mothers of students with disabilities. The researcher developed a burnout Scale which consists of (19) items and a perceived self-competence Scale which consists of (20) items. A correlation descriptive design was used. The results showed that the level of burnout was low (Mean= 2.30), while the level of burnout was high (Mean= 3.87). Regarding the correlation coefficient, the results showed that there was a significant negative correlation between burnout and perceived self-competence. According to regression, the results showed that burnout predicts (37%) of perceived self-competence among mothers of students with disabilities in the Sultanate of Oman (R2=0.037).